Workshop examines ways to conserve East Africa’s animal genetic resources - Okeyo Mwai, Ally (International Livestock Research Institute, 2010)
Okeyo Mwai from ILRI's Biotechnology Theme reflects on a December 2010 workshop on ex-situ conservation of animal genetic resources in Eastern and Central Africa.